2020
DOI: 10.1001/jamapediatrics.2019.4368
|View full text |Cite
|
Sign up to set email alerts
|

Association of Comorbid Mood and Anxiety Disorders With Autism Spectrum Disorder

Abstract: IMPORTANCEIt is critical to evaluate the risk of comorbid psychiatric diagnoses to meet the needs of individuals with autism spectrum disorder (ASD).OBJECTIVE To examine whether individuals with ASD are at greater risk for comorbid diagnoses of depression, anxiety, or bipolar disorder. DESIGN, SETTING, AND PARTICIPANTSThis cohort study used data from a population-based birth cohort of 31 220 individuals born in Olmsted County, Minnesota, from January 1, 1976, to December 31, 2000. Patients with research-identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
67
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 36 publications
4
67
0
Order By: Relevance
“…Moreover, an overstretched healthcare system paired with social distancing rules meant that many adults with autism lost some, if not all of the support they received before the pandemic, as evident from both our quantitative and qualitative results. These results are particularly worrisome considering that adults with autism ordinarily have higher rates of anxiety and depression than neurotypicals (18,19), as was also reported by participants in our sample, and struggle to access mental health services (37,38). These results are in line with a recent report from the National Autism Society (39), where 9 out of 10 people with autism indicated to worry about their mental health during lockdown.…”
Section: Mental Healthsupporting
confidence: 90%
See 2 more Smart Citations
“…Moreover, an overstretched healthcare system paired with social distancing rules meant that many adults with autism lost some, if not all of the support they received before the pandemic, as evident from both our quantitative and qualitative results. These results are particularly worrisome considering that adults with autism ordinarily have higher rates of anxiety and depression than neurotypicals (18,19), as was also reported by participants in our sample, and struggle to access mental health services (37,38). These results are in line with a recent report from the National Autism Society (39), where 9 out of 10 people with autism indicated to worry about their mental health during lockdown.…”
Section: Mental Healthsupporting
confidence: 90%
“…It is important to note that although the groups did not differ on common matched-for variables such as age, gender ratio, and years of education (taken as a rough proxy for SES (46)), there were differences between groups on other variables such as preexisting mental health difficulties and employment status, with adults reporting more mental health difficulties and lower employment status. However, these differences are representative of what is generally found in the autism population (18,19,40). Moreover, this makes the greater pandemic related increase in mental health problems as found for adults with autism even more worrisome.…”
Section: Strengths and Limitationsmentioning
confidence: 75%
See 1 more Smart Citation
“…Particularly it is reported that around 70% of individuals with autism spectrum disorder might also fulfill the criteria for another co-morbid mental disorder and approximately 40% can have two or more co-morbid mental disorders (1). Common comorbid conditions include anxiety disorders, epilepsy, depression, gastrointestinal symptoms, challenging behavior, sleep problems, toileting, and feeding issues (31)(32)(33)(34)(35)(36), as well as Attention-Deficit/Hyperactivity Disorder (ADHD) (37). Interestingly, even before DSM-V, studies have reported ADHD traits in populations with autism spectrum disorder in the areas of attention and social cognition (38).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, people who are FMR1 premutation carriers exhibit higher rates of MDD and depressed mood compared to the general population [17][18][19] . Additionally, people with ASD have an increased risk of developing MDD by the time they are 30 years old compared to people without ASD 20 . Moreover, caretakers of people with FXS identify mood and depression as a priority for treatment development 21 .…”
Section: Introductionmentioning
confidence: 99%